Network Meta-Analysis of Effectiveness of First-Line Immunotherapy Treatments for Patients with Brain Metastases from Advanced Non-Small Cell Lung Cancer - JIA Muyuan; ZHANG Hongjun; LI Lin; WU Jianhui; GONG Huanhuan; REN Bowen; LIU Han (Zhongliu Fangzhi Yanjiu, 2024)
Objective To conduct a network meta-analysis on the effectiveness of first-line immunotherapy on patients with brain metastases from advanced non-small cell lung cancer (NSCLC). Methods Two investigators conducted a computerized search of Pubmed, Embase, Cochrane, and other databases to screen the literature, extract the information, and assess the risk of bias of the included studies. The included clinical trials were statistically analyzed using R (4.1.3) software. For the study outcome indicators OS and PFS, the risk ratios (HRs), and the 95% confidence intervals (CIs) were extracted from the included studies and logarithmically transformed into effect analysis statistics. Results Six randomized controlled trials were finally included, including 327 patients with non-excludable NSCLC brain metastases. Network meta-analysis suggested that PD-1 inhibitor + CTLA-4 was more advantageous than the conventional chemotherapy for enhancing patients’ OS (HR: 0.13, 95%CI: 0.03-0.71), followed by PD-L1 inhibitor (HR: 0.17, 95%CI: 0.04-0.74) and PD-1 inhibitor + chemotherapy (HR: 0.36, 95%CI: 0.2-0.63). PD-1 inhibitor + CTLA-4 was also more advantageous (HR: 0.37, 95%CI: 0.15-0.93) than the conventional chemotherapy for boosting patients’ PFS, followed by PD-L1 inhibitor + chemotherapy (HR: 0.44, 95%CI: 0.29-0.66) and PD-1 inhibitor (HR: 0.48, 95%CI: 0.27-0.86). Conclusion Immune checkpoint inhibitor therapy improves the survival of patients with brain metastases from advanced NSCLC. In particular, the combination of PD-1 inhibitor and CTLA-4 inhibitor show excellent survival benefit.